Fire Resistance Analysis of Two-Way Reinforced Concrete Slabs - Fidan Salihu; Zijadin Guri; Meri Cvetkovska; Fatos Pllana (Civil Engineering Journal, 2023)
This paper presents a fire resistance analysis of two-way reinforced concrete (RC) slabs. The study analyzes the effect of specific parameters—concrete cover thickness, span, and support conditions—on the fire resistance of the slabs. To that end, the slabs were exposed to Standard Fire ISO 834, and the 3D nonlinear numerical analyses were conducted in SAFIR2016. The results of the numerical analyses were evaluated against experimental results reported in the literature. The agreement between the two sets of results was satisfactory throughout the fire test. Nonetheless, to verify the obtained numerical results, all testing-related parameters must comply with the numerical simulation results. This comparison demonstrated the usefulness of numerical simulations in predicting the behavior of structures in fire conditions. In addition to the nonlinear numerical analysis, the fire resistance was calculated using the simplified method and tabulated data described in Eurocode 2 (Part 1.2) to assess the accuracy and reliability of fire safety regulations in the design of two-way slabs and identify significant differences between the design code and numerical analysis. The comparison showed that SAFIR2016 provides more accurate results by considering additional factors, such as tensile membrane forces, which increase the fire resistance of two-way slabs. According to the load-bearing criteria, the two-way slabs have high fire resistance, considerably higher than prescribed in the fire safety regulations, which ignore the positive effect of tensile membrane forces. According to the numerical analysis, the upper reinforcement in the compression areas of the slab's span was considered, which increased the fire resistance of the slabs. In contrast, according to the design codes, the contribution of this reinforcement is neglected. It was indicated that the increased concrete cover improves the fire resistance of the slabs. The vertical displacements increase by increasing the slab span, but according to the load-bearing criteria, all the slabs show fire resistance of over ten hours. In terms of bearing capacity, slabs with various support conditions show fire resistance of longer than ten hours. In terms of deflections, the supporting conditions of the slabs have a significant influence on their behavior. This study provides valuable insights into the fire resistance of two-way RC slabs and highlights the importance of considering specific parameters in the analysis. Doi: 10.28991/CEJ-2023-09-05-05 Full Text: PDF